Prevalence Of Preoperative Anxiety And Its Causes Among Surgical Patients Presenting In Rawalpindi Medical University And Allied Hospitals, Rawalpindi - Arshia Kanwal , Ayesha Asghar , Ayesha Ashraf , Abdul Qadoos, Arshia Kanwal , Ayesha Asghar , Ayesha Ashraf , Abdul Qadoos (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Anxiety is defined as a futureoriented mood state during which one is prepared to attempt to address approaching negative events. Stress in patients planning surgery in important as it can influence their decision to seek or delay medical care. The aim of the study was to determine the prevalence and factors causing anxiety in preoperative period in patients undergoing major elective surgery procedures. Materials and Methods: This multi-centered cross-sectional study was carried out Rawalpindi medical university allied hospitals from January 2018 to June 2018. We selected 363 patients of elective hernia repair surgery and thyroid surgery for the study. Structured Performa was used to obtain demographic data and factors contributing to anxiety. Visual analogue scale (VAS) was used to measure anxiety and a score of ≥45 was considered as high anxiety. Data was entered and analyzed using the statistical package for social sciences (SPSS) software, version 22.Two sided Chi square test was used to determine the statistical significance between anxiety and gender Results: 228 (62.8 %) patients had preoperative anxiety score > 45. There was significant correlation (x2=0.005) between female gender and preoperative anxiety. Among the common reasons for preoperative anxiety in respondents were the fear of surgery being postponed 240 (69.9%), Nakedness on operating table 207 (57.7%) Not waking up from surgery 194 (54%), Inability to pay hospital bills 193 (53.8%). Conclusion: Patients in our setting experience significantly high levels of preoperative anxiety.